2014
DOI: 10.2308/accr-50861
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Consequences of Lowering Disclosure Thresholds

Abstract: In recent years, regulators have considered several initiatives to lower the threshold for disclosing risks to investors. We examine two ways in which disclosing more risks can actually lower investors' perceptions of risk. Utilizing an experiment, we find evidence of two unintended consequences on different types of investors. First, we demonstrate that the addition of low-probability risks to a disclosure can dilute (rather than add to) more probable losses, leading certain investors to lower their perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In prior auditing research on the dilution effect, researchers required their participants to make probabilistic judgments about fraud (Hackenbrack 1992;Hoffman and Patton 1997;Wood 2012; Lambert and Peytcheva 2017), risk disclosure thresholds (Fanning et al 2015), goingconcern (Shelton 1999;Lambert and Peytcheva 2017), and to assess the risk of material misstatements in accounts receivable (Glover 1997;Waller and Zimbelman 2003). KME show 5 See Igou (2007) and Kemmelmeier (2007a, b) for an exchange on which approach has the most empirical support.…”
Section: Hypothesis and Research Questionmentioning
confidence: 99%
See 4 more Smart Citations
“…In prior auditing research on the dilution effect, researchers required their participants to make probabilistic judgments about fraud (Hackenbrack 1992;Hoffman and Patton 1997;Wood 2012; Lambert and Peytcheva 2017), risk disclosure thresholds (Fanning et al 2015), goingconcern (Shelton 1999;Lambert and Peytcheva 2017), and to assess the risk of material misstatements in accounts receivable (Glover 1997;Waller and Zimbelman 2003). KME show 5 See Igou (2007) and Kemmelmeier (2007a, b) for an exchange on which approach has the most empirical support.…”
Section: Hypothesis and Research Questionmentioning
confidence: 99%
“…Hoffman and Patton (1997) proposed several steps to mitigate the dilution effect, such as making auditors aware of the issue and developing decision aids. Lastly, Fanning et al (2015) found that directional goals can ameliorate the dilution effect when investors are presented with post-decisional information in the context of litigation risk assessments. In the current study, we propose an alternative approach (i.e., use of a frequency response mode) to mitigate the dilution effect in auditors' fraud risk judgments.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations